Challenges of Special Education Teachers in HOTS (Higher Order Thinking Skills) Based Learning for Students with Special Needs in Lampung Province - Sani, Yulvia; Wardany, Ossy Firstanti; Devita, Dela; Herlina, Heni; Vernanda, Genesa (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The research aims to identify the perspectives and challenges special education teachers face when learning HOTS (Higher-order thinking skills) for students with special needs at the elementary level in Lampung Province. This research uses a survey-type quantitative approach with Google Forms. Twenty-nine special school teachers were respondents by random sampling. The study's results found that all of the teachers knew the concept of HOTS-based learning. As many as 69% of teachers thought that HOTS-based learning could be applied to every type of ABK, and the rest answered no. However, 66% of teachers have implemented HOTS-based learning for students with special needs. This research explores the perceptions, experiences and obstacles of teachers who have implemented HOTS for children with special needs in Lampung. Based on research, Teachers admit they need training, good facilities and infrastructure, peer support, parental support, and reading resources. Recommendations for overcoming this challenge include increasing teacher training, allocating sufficient resources, and supporting and collaborating between the government, schools, and the community. Apart from that, HOTS is indeed a good concept, but this research also shows that HOTS is one of many things that teachers should implement. The implementation of HOTS must be appropriate to the needs and abilities of each child with different special needs.